A novel cell culture model as a tool for forensic biology experiments and validations. (September 2016) - Feine, Ilan; Shpitzen, Moshe; Roth, Jonathan; Gafny, Ron
Highlights: An experimental model based on cultured human dermal fibroblasts was developed. This model involves low variance and simplifies the design of touch DNA experiments. Comparative tape-lifting and UV decontamination studies were carried out. Owing to the low variance reference material, clear conclusions could be drawn. Abstract: To improve and advance DNA forensic casework investigation outcomes, extensive field and laboratory experiments are carried out in a broad range of relevant branches, such as touch and trace DNA, secondary DNA transfer and contamination confinement. Moreover, the development of new forensic tools, for example new sampling appliances, by commercial companies requires ongoing validation and assessment by forensic scientists. A frequent challenge in these kinds of experiments and validations is the lack of a stable, reproducible and flexible biological reference material. As a possible solution, we present here a cell culture model based on skin-derived human dermal fibroblasts. Cultured cells were harvested, quantified and dried on glass slides. These slides were used in adhesive tape-lifting experiments and tests of DNA crossover confinement by UV irradiation. The use of this model enabled a simple and concise comparison between four adhesive tapes, as well as a straightforward demonstration of the effect of UV irradiation intensities on DNA quantity and degradation. In conclusion, we believe this model has great potential to serve as an efficient research tool in forensic biology.